COMMAND DIRECTIVE ILLOCUTIONARY ACT DISCOVERED IN CENTRAL INTELLIGENCE MOVIE - Suma, Yoga Pramarta (Journal of Humanities, Social Science, Public Administration and Management (HUSOCPUMENT), 2024)
Abstract— this research is entitled “Command Directive Illocutionary Act Discovered in Central Intelligence Movie by Rawson Marshall. This study aims to determine the directive illocutionary speech acts and the context of the situation in the directive illocutionary speech acts expressed by the characters in the film. The directive illocutionary acts are discussed using the theory of directive illocutionary acts proposed by Kreidler (1998: 189-190). The context of the situation is discussed using the situational context theory proposed by Halliday and Hasan (1985: 12). In collecting data, first, the writer watches the movie and marks the utterances that contain the illocutionary act of directive commands in the film script. The method used in analyzing the data is a qualitative descriptive method. The writer classifies the data based on the sentence structure of the directive illocutionary acts of commands and then analyses the context of the situation. In presenting the findings, formal and informal methods are used. The formal method is used to show the percentage of the sentence structure of directive illocutionary acts using tables, and the informal method is used to describe the data descriptively through words. In this study, 21 data were found regarding illocutionary acts of directive command.